No significant association between term premature rupture of membranes and neonatal APGAR score: A cross-sectional study - Shelvy Era Chintia; Henidekasari; Veronica Ela Rimawati; I Nengah Budiarta (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Premature rupture of membranes (PROM) is defined as the rupture of the amniotic sac before the onset of labor, potentially increasing the risk of infection, hypoxia, and a low APGAR score in newborns. The APGAR score assesses neonatal health immediately after birth and can be influenced by maternal and delivery factors, including the duration of PROM. Methods: This analytical observational study employed a cross-sectional design and involved 119 term-pregnant women with PROM, selected through purposive sampling from medical records at Dr H. Abdul Moeloek Regional General Hospital, Lampung Province, in 2024. The independent variable was PROM duration (<12 hours or >12 hours), and the dependent variable was the neonatal APGAR score (>7 or <7). Data analysis employed the Chi-square test with a 95% confidence level. Results: Most respondents (83.2%) experienced PROM lasting <12 hours, and 79% of newborns had APGAR scores >7. Chi-square analysis revealed no statistically significant association between PROM duration and APGAR score (p = 0.092; OR = 0.93). Although a higher proportion of low APGAR scores occurred in the >12-hour PROM group, the relationship was not statistically significant. Conclusion: The study indicates no significant correlation between PROM duration in term pregnancies and neonatal APGAR scores. Prompt medical interventions may mitigate potential risks, reducing the impact of PROM duration on immediate neonatal outcomes. These findings underscore the importance of timely obstetric management and suggest that further research with larger sample sizes is warranted to investigate other potential contributing factors.